Modern methods of treating marijuana addiction (cannabis use disorders) and its influence on health - Kapłan, Wojciech; Zalewa, Karolina; Rachwał, Dominika; Bartoszek, Lidia; Olszak, Joanna; Rogowska, Monika; Świdziński, Rafał; Lipiec, Jakub; Skorupski, Bartosz; Piątek, Ewa (Journal of Education, Health and Sport, 2023)
Introduction: Worldwide, cannabis is the most widely used illegal psychoactive substance and the third most common drug, after alcohol and tobacco. Cannabis use disorder (CUD) affects approximately 10% of the 193 million cannabis users worldwide. In recent years, cannabinoids have become more and more popular. The CUD is becoming a growing social and health problem. The search for effective forms of pharmacotherapy is still ongoing, and an effective combination of psychotherapy and pharmacotherapy may be crucial for the future of CUD treatment. Material and method: The article was based on a review and analysis of publications and discoveries in recent years, which were available in the PubMed and Google Scholar database. Results: 82 study participants attempted abstinence from cannabis use. In the final primary endpoint analysis, both 400 mg of CBD and 800 mg of CBD were more effective than placebo in reducing cannabis use. 50 people who were addicted to cannabis treated with gabapentin showed a significant reduction in cannabis use and cannabis withdrawal compared to placebo. Moreover, 70 men addicted to cannabis were randomized and those, who used FAAH inhibitors reported fewer cannabis withdrawal symptoms, less cannabis use and lower THC urine levels than placebo users. Conclusions: Gabapentin has been proven to show a reduction in CUD. The use of CBD, FAAH inhibitors and psychotherapy MET/CBT/CM also appear to be effective. In addition, the use of the principles of People-First Language, avoiding slang and idioms, using medical and curing vocabulary, respects the addicted person, and also positively influences the chances of abstinence.